2018
DOI: 10.1519/jsc.0000000000002772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Accentuated Eccentric Loading on Muscle Properties, Strength, Power, and Speed in Resistance-Trained Rugby Players

Abstract: Douglas, J, Pearson, S, Ross, A, and McGuigan, M. Effects of accentuated eccentric loading on muscle properties, strength, power, and speed in resistance-trained rugby players. J Strength Cond Res 32(10): 2750-2761, 2018-The purpose of this study was to determine the effects of slow and fast tempo resistance training incorporating accentuated eccentric loading (AEL) compared with traditional resistance training (TRT) in trained rugby players. Fourteen subjects (19.4 ± 0.8 years, 1.82 ± 0.05 m, 97.0 ± 11.6 kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 40 publications
1
65
1
1
Order By: Relevance
“…Acknowledging again that due to the ECC force-velocity relationship, these two conditions are not mutually exclusive [4]. While much of the research investigating the effects of ECC training have recruited untrained subjects, improvements in hypertrophy and strength have also been observed in strength-trained participants [7,47]. In addition to increases in strength, improved muscle power output, as assessed under CON-only and SSC (i.e., ECC/CON) conditions, has also been demonstrated [9,48].…”
Section: Physiological Rationale For Incorporating Eccentric Resistanmentioning
confidence: 99%
“…Acknowledging again that due to the ECC force-velocity relationship, these two conditions are not mutually exclusive [4]. While much of the research investigating the effects of ECC training have recruited untrained subjects, improvements in hypertrophy and strength have also been observed in strength-trained participants [7,47]. In addition to increases in strength, improved muscle power output, as assessed under CON-only and SSC (i.e., ECC/CON) conditions, has also been demonstrated [9,48].…”
Section: Physiological Rationale For Incorporating Eccentric Resistanmentioning
confidence: 99%
“…As higher magnitudes of ECC work have been observed even when the ECC overload was only applied to the first repetition within a straight set, [68], the set structure may not need to be altered in order to produce this potentially favorable tension profile. While Douglas and colleagues [69] recently demonstrated that AEL improved muscle strength independent of size changes, Shoenfeld and Grgic [70] recently suggested that conservative usage of ECC overload may be enough to augment muscle hypertrophy. Taken together, the maintenance of the set structure is likely to be most beneficial for work capacity adaptations, while supramaximal AEL may be the most beneficial for inducing muscle size changes.…”
Section: Accentuated Eccentric Loadingmentioning
confidence: 99%
“…Additionally, most training processes are multi-factorial in nature and coexist alongside a technical and tactical development process. When AEL has been programmed alongside a multi-factorial process, it has diminished sprint ability and strength performance, most likely due to the concurrent nature of the training suppressing potentially favorable effects of AEL [69]. Therefore, strength and conditioning practitioners should be cognizant of the overall volume and total load relative to prior phases in the prescription of AEL with the desired outcome of maximal strength changes.…”
Section: Accentuated Eccentric Loadingmentioning
confidence: 99%
“…However, the use of very heavy loads during single limb movement could cause misalignment of the spine, pelvis and shoulder girdle during upper or lower limb exercise, thereby heightening the risk of injury. This might be more problematic for those who are less accustomed to high-intensity eccentric exercise, although the advent of specific eccentric devices or custom built machines can aid the application of high-intensity eccentric training stimuli [11,12,17,31]. This approach is likely to be the most efficient and safest options for the application of high-intensity eccentric stimulus during multi-joint exercise to offer a sufficient eccentric training stimulus to strong athletes.…”
Section: Some Investigators Have Successfully Employed An Eccentric Ementioning
confidence: 99%
“…Often, the current body of research pertaining to high-intensity eccentric resistance training employs non-athletic populations that are prescribed training in a manner that is removed from a high-performance environment. However, there are a few limited examples where higher intensity eccentric training has been employed in trained populations [5,8,11,26], but in general there is a dearth of information that could be of value to elite athletes. Importantly, the current body of evidence has limited potential to understand the application for training prescription and adaptation in an athletic population.…”
Section: Introductionmentioning
confidence: 99%